2013
DOI: 10.1177/0021998313498791
|View full text |Cite
|
Sign up to set email alerts
|

Effect of data reduction and fiber-bridging on Mode I delamination characterization of unidirectional composites

Abstract: Reliable delamination characterization data for laminated composites are needed for input in analytical models of structures to predict delamination onset and growth. The double-cantilevered beam (DCB) specimen is used to measure fracture toughness, G Ic , and strain energy release rate, G Imax , for delamination onset and growth in laminated composites under mode I loading. The current study was conducted as part of an ASTM Round Robin activity to evaluate a proposed testing standard for Mode I fatigue delami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 6 publications
3
55
0
Order By: Relevance
“…[47,48] were the first to note that, for a given R-ratio, the da/dN versus G max curve determined from DCB tests subjected to fatigue loading was not unique but depended on the starting value of G max . This dependency was subsequently confirmed in [4,42]. As a result it has been argued [47,48] that for real aircraft structures (from a design and from a sustainment/maintenance perspective) it is important to use the da/dN versus G max curve which has the fastest growth rate and a means for determining this curve was proposed.…”
Section: Effect Of the Starting Value Of G Maxmentioning
confidence: 85%
See 4 more Smart Citations
“…[47,48] were the first to note that, for a given R-ratio, the da/dN versus G max curve determined from DCB tests subjected to fatigue loading was not unique but depended on the starting value of G max . This dependency was subsequently confirmed in [4,42]. As a result it has been argued [47,48] that for real aircraft structures (from a design and from a sustainment/maintenance perspective) it is important to use the da/dN versus G max curve which has the fastest growth rate and a means for determining this curve was proposed.…”
Section: Effect Of the Starting Value Of G Maxmentioning
confidence: 85%
“…Here it should be recalled that, when originally formulating the equations for crack growth, Paris argued that, since Irwin [20,21] had shown that the stress-intensity factor, K, uniquely characterises the near tip stress field, then the rate of FCG should be a function of ΔK and K max [22,23]. In [24] [2,[41][42][43][44][45][46][47][48][49][50][51][52][53][54][55]. (Where ∆√G is given by (�G max -�G min ); and G min is the minimum value of the energy release-rate in a fatigue cycle.…”
Section: Analysis Of the Measured Fcg Datamentioning
confidence: 99%
See 3 more Smart Citations